Pemanfaatan Blog Sebagai Media Pengetahuan Dan Bisnis Pada PKK Desa Sei Silau Timur - Mulyani, Neni; Hutahaean, Jeperson; Azhar, Zulfi; Yuliana, Siska; Farenza, Dinda Novri (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The existence of blog media in disseminating information is a means of storing information online that can be used by staff so that they can provide all information without space and time limits. The PKK of East Sei Silau Village, Asahan Regency, has several active activities carried out in several places in its environment. In carrying out these activities, they still use devices manually to provide information in their activities. The aim of carrying out this service activity is to find out the use of blogs in the business and economic category, to find something unique about blogs that can be published to various parties regarding the use of business and economic blogs so that they can be used effectively and more usefully. The activity implementation method used was in the form of training, interactive discussions with the entire PKK team in East Sei Silau Village, Asahan Regency. This activity uses theoretical and practical knowledge in the room. As a result of the final assessment of the activity, the participants were able to understand the material presented based on the results of the assessment scores obtained from the posttest test results. The activity material given to participants can be used and utilized in creating a blog. The material presented to participants reached 90% of all the concepts involved in creating blogs. The delivery of the material consists of several sessions, namely: explanation, practice, and discussion.